If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 8 = 4x + 6 Reorder the terms: 8 + 9x = 4x + 6 Reorder the terms: 8 + 9x = 6 + 4x Solving 8 + 9x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + 9x + -4x = 6 + 4x + -4x Combine like terms: 9x + -4x = 5x 8 + 5x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + 5x = 6 + 0 8 + 5x = 6 Add '-8' to each side of the equation. 8 + -8 + 5x = 6 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = 6 + -8 5x = 6 + -8 Combine like terms: 6 + -8 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4
| 170*1.6= | | 7x/2^x | | 5/3n=40 | | 6y^2-10y= | | -[3(-3*1)(2)-4]+4= | | 3x-1-4x=-2x+7x-3 | | 4/636 | | [-(3-2)(-2)]= | | 6x^2+36+30=0 | | 2n+14=101 | | -3(x-4)=16 | | -1/17p=-6 | | 5(-31)+22=(-10)+6 | | 3x+-2=2(x+5)+x | | 2a(a+-5)+4(a+-5)= | | (3x-4)(2-x)= | | 3x-2=2(x+5)+x | | 10/3m=-5/6 | | 6/z=12/5 | | 3x=4x-27 | | -[-(-p)]-(-4)(-2-p)=-(4-2p) | | 2(x+4)+2x=100 | | -x+2=-14 | | 48*3.5= | | 2r-2=100 | | .72x=216 | | -3[(-4-2)-(-2-1)-1]= | | [(-4-2)-(-2-1)-1]= | | [(-2)-(-2-1)]= | | 2r+2=100 | | 9(-3)+3(-3-9)= | | -3(x-12)=18 |